The REACH baseline study: a tool to monitor the new EU policy on chemicals (Luxembourg, 2009)
"It lays out a foundation for future studies using a set of indicators, in order to monitor the success of REACH. Three main indicators most closely related to the main objectives of REACH were noted: administrative indicators, risk & quality indicator system and supplementary indicators. The study will monitor changes to risk and the current information base on chemicals, including the quality of such information. The study noted the difficulty in tracking risk reduction and used a subset of chemicals taken out of the approximately 30,000 chemicals regulated under REACH."